2013
DOI: 10.1111/anec.12108
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability and Heart Rate Turbulence in Patients with Hematologic Malignancies Subjected to High‐Dose Chemotherapy in the Course of Hematopoietic Stem Cell Transplantation

Abstract: In patients with hematopoietic malignancies treated with HSCT, decreased HRV and HRT were observed after chemotherapy and stem cells administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
4
8
0
Order By: Relevance
“…The worsening of HRV parameters in our study persisted until the end of chemotherapy. Our findings are consistent with those of other researchers, who showed a decrease in HRV parameters [7], suggesting the possibility of worsening sympathetic activation after drug infusion. It should be noted that Holter ECG was performed immediately after drug infusion, and many side effects of anti-cancer drugs are more strongly expressed in this period than a few weeks after administration.…”
Section: Discussionsupporting
confidence: 93%
“…The worsening of HRV parameters in our study persisted until the end of chemotherapy. Our findings are consistent with those of other researchers, who showed a decrease in HRV parameters [7], suggesting the possibility of worsening sympathetic activation after drug infusion. It should be noted that Holter ECG was performed immediately after drug infusion, and many side effects of anti-cancer drugs are more strongly expressed in this period than a few weeks after administration.…”
Section: Discussionsupporting
confidence: 93%
“…Further declines in heart rate variability after transplantation appear minor, unlike in adults. 10 Heart rate variability decreases with age 22,23 from childhood. 24 Infants have high sympathetic activity that decreases quickly between the ages of 5 and 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…18 An earlier investigation for adults which evaluated haematopoietic stem cell transplantation revealed changes in heart rate variability and heart rate turbulence, both of which were attributed to the transplantation procedure. 10 The use of cyclophosphamide, total body irradiation, and cytokines 19,20 should be considered as well in understanding the complex mechanisms of decreased heart rate variability. Although not investigated in the cohort, mental stress associated with treatment and diminished exercise tolerance due to long-term hospitalisation might also have affected autonomic nervous function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, the detailed range of possible cardiovascular complications and potential cardiotoxic effects of the stem cell administration in individual groups of patients remains unknown. Our previous studies showed that in patients with hematopoietic malignancies undergoing HSCT, after chemotherapy and stem cell administration, the decreased heart rate variability and heart rate turbulence were observed [ 3 ].…”
Section: Introductionmentioning
confidence: 99%